2017
DOI: 10.1007/s12298-017-0495-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes from the ICE–CBF–COR pathway under cold stress in Aegilops–Triticum composite group and the evolution analysis with those from Triticeae

Abstract: Adverse environmental conditions limit various aspects of plant growth, productivity, and ecological distribution. To get more insights into the signaling pathways under low temperature, we identified 10 C-repeat binding factors (), 9 inducer of CBF expression () and 10 cold-responsive () genes from - composite group under cold stress. Conserved amino acids analysis revealed that all CBF, ICE, COR contained specific and typical functional domains. Phylogenetic analysis of CBF proteins from showed that these CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 80 publications
1
34
0
1
Order By: Relevance
“…Secondly, based on the currently known protein sequences of the COR / ICE genes of barley and rice, the HMM model was constructed. By searching with this model, the wheat COR and ICE protein was obtained again (Jin et al, 2018). After repetitive sequences were removed, COR and ICE protein sequences were predicted among the remaining sequences.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, based on the currently known protein sequences of the COR / ICE genes of barley and rice, the HMM model was constructed. By searching with this model, the wheat COR and ICE protein was obtained again (Jin et al, 2018). After repetitive sequences were removed, COR and ICE protein sequences were predicted among the remaining sequences.…”
Section: Methodsmentioning
confidence: 99%
“…The ICE-CBF-COR pathway is a universal pathway related to cold stress tolerance in crop species (Wang et al, 2017a; Jin et al, 2018). ICE (inducer of CBF expression) genes are members of the MYC family of transcription factors, and MYC is a subfamily of bHLH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that MYC2, as a key transcriptional activator of JA responses, can activate gene SAG29 ( SENESCENCE-ASSOCIATED GENE29 ) from Arabidopsis by binding to its promotor and promote JA-induced leaf senescence, whereas another group of bHLH transcription factors (bHLH03, 13, 14 and 17) can bind to the promotor of SAG29 to counteract the enhancing effect of MYC2/MYC3/MYC4, thus these signaling components form an elegant feedback regulation mechanism to modulate JA-induced senescence (Qi et al, 2015). The pathway that is composed of the Inducer of CBF Expression (ICE), CBF transcription factors, and various Cold Regulated (COR) genes is the best-studied cold response pathway (Wang et al, 2017; Jin et al, 2018). Recently, more evidence was obtained for the direct interaction between JA signaling and the ICE-CBF-COR signaling cascade.…”
Section: Jasmonatesmentioning
confidence: 99%
“…It is an adaptive response where plants increase freezing tolerance after exposure to low non-freezing temperatures [19]. The CBF/DREB protein, a DNA binding protein belonging to AP2/ERF superfamily, was first identified in A. thaliana as a LT-induced transcription factor [20]. APETALA2/ethylene-responsive element binding factor (AP2/ERF) family is a large class of plant-specific transcription factors, including AP2, RAV, ERF and CBF (C-repeat binding factor) [21,22].…”
Section: Introductionmentioning
confidence: 99%